Gender Trouble in Hongkong Cinema - Cheung, Tammy; Gilson, Michael (Cinémas, 1993)
The authors conduct a brief survey of some recent examples of the Hongkong cinema, focusing on questions surrounding the portrayals of female and male characters in them. Today's Hongkong films, society and culture are just now taking tentative steps towards an awareness of gay and lesbian themes, and in some measure, of feminism. How are different types of female characters presented in contemporary Hongkong cinema? How does the traditional Chinese view of "male" differ from the West's? The recent trend that has "gender-bending" characters appearing in a number of Hongkong feature films is also examined. The authors maintain that stereotypical representations of women, men, and homosexual characters persist in the Hongkong film industry, that honest portrayals of gay and lesbian characters are mostly absent from the movie screens of the Crown Colony.